Effectiveness of a Multidisciplinary Rehabilitation Program Following Shoulder Injury - Andrea Bean; Cathryn Edmonds; Tukata Lin; Rachel Davis; Lisa Hopcroft; Alicia Savona; Gargi Singh; Kristina Boccia; Kyle Leming; Helen Mann; Helen Razmjou (Scholarworks @ WMU, 2017)
Background: Shoulder injuries in working age adults result in a major cost to the health care system. The purpose of this study was to examine the effectiveness of a new multidisciplinary rehabilitation program and to explore factors that affected a successful return to work (RTW) in injured workers with shoulder problems who received this program. Methods: This was a prospective longitudinal study. The patient-oriented outcome measures were the Numeric Pain Rating Scale (NPRS) and the Disabilities of the Arm, Shoulder, and Hand (DASH). Range of motion (ROM) in flexion, abduction, and external rotation and strength in lifting and push/pull were documented. All outcomes were measured before and at the completion of the program. Results: Data of 68 patients were used for analysis. All outcomes showed a statistically significant improvement over time. Conclusions: Multidisciplinary rehabilitation programs help to improve pain, disability, ROM, strength, and facilitate RTW. Higher stress and a fast-paced work environment increased the risk of not progressing in work status.